(untitled) (Research, Society and Development, 2021)
Goal: To assess body mass index (BMI) changes in people living with HIV (PLHIV) and using antiretroviral therapy (ART) with dolutegravir (DTG) and its associated factors. Methods: Retrospective and prospective cohorts of PLHIV who started ART with DTG or used DTG after changing the therapeutic regimen, from Belo Horizonte, between February/2017 and March/2020. Data were gathered from clinical records of the Drug Logistics and Laboratory Test Control Systems. BMI changes were analyzed in the following week intervals 1-24(t24), 25-48(t48), 49-72(t73), and 73-96(t96) using the Wilcoxon test and generalized estimation equation (GEE) model, at 5% significance level. Results: A total of 614 individuals were included and average was 38.4 years old. Most were men (85.5%) and 52.3% had started ART with DTG. These individuals, and the immunosuppressed ones, showed significant increases in BMI when compared to those who used DTG after switching therapeutics or the non-immunosuppressed ones (p-value <0.05). After 96 weeks, individuals starting ART with DTG had a mean increase in BMI of 1.02 Kg/m2, whereas those who used DTG after the therapeutic change had an increase of 0.56 Kg/m2 (p<0.05). DTG use length, ART type, immune status, baseline BMI, and age were associated (p<0.05) with BMI increases. Conclusions: We observed an increase in BMI both in individuals starting ART with DTG use and those using it after changing the therapeutic regimen.